Molecular detection of field predation among larvae of two ladybird beetles is partially predicted from laboratory experiments - Gabriele Rondoni (Nature Portfolio, 2018)
Abstract Despite the fact that natural enemies can synergistically contribute to herbivore pest suppression, sometimes predators engage in intraguild predation (IGP) that might dampen trophic cascades. DNA-based gut-content analysis has become common in assessing trophic connections and biocontrol potential by predators in field systems. Here, we developed a molecular technique that can be used to unravel predation among two ladybirds, Coccinella septempunctata and Hippodamia variegata, and their shared prey, Aphis gossypii. Both ladybirds may provide effective control of the pest. Therefore, understanding their likelihood to engage in IGP is crucial for conservation biological control. Ladybird specimens were collected in melon crop. DNA extraction, primer design and evaluation were conducted. Detectability of prey DNA did not differ significantly between the two ladybirds. H. variegata exhibited higher predation on A. gossypii than C. septempunctata (90.6% vs. 70.9%) and data correction based on DNA detectability confirmed this ranking. IGP was similar among the two species, although corrected data might suggest a stronger predation by C. septempunctata. Intriguingly, IGP by C. septempunctata was lower than predicted by laboratory bioassays, possibly due to the high complexity that arises under field conditions. Implications of our results for biological control and perspectives for ecological network analysis are discussed.